ANALISIS PENGARUH JUMLAH UNIT USAHA, NILAI EKSPOR, DAN PERTUMBUHAN EKONOMI TERHADAP PENYERAPAN TENAGA KERJA SEKTOR UMKM DI INDONESIA - martin Luter purba; demak sinta buulolo; Jusmer Sihotang (Fakultas Ekonomi dan Bisnis, Universitas HKBP Nommensen, 2020)
This study uses multiple linear regression models. The data used is secondary data from the Central Statistics Agency (processed data) and the Ministry of Cooperatives and SMEs (processed data), namely the number of business units, export value, economic growth and the absorption of labor in the MSME sector. Data collection starts from 1998 to 2018. The data analysis used is the multiple linear regression analysis method. The results show that the increasing number of business units will affect increasing the absorption of labor in the MSME sector in Indonesia, the increased export value will affect decreasing the employment of the MSME sector in Indonesia but not significantly, and the increasing economic growth in Indonesia will affect increasing absorption of workforce in the UMKM sector. Based on the results, I can suggest it that the government should encourage the number of business units by cutting interest rates and providing MSME tax relief, business licensing that is not long and easy. Then to increase the export value the government needs to develop human resources. To increase and maintain Indonesia’s economic growth, the government needs to monitor the products produced by MSME players in order to prevent overproduction.